PELANGGARAN PRINSIP KERJA SAMA PADA PERCAKAPAN DALAM PEMBELAJARAN BAHASA INDONESIA SISWA KELAS VIII DI SMP NEGERI 3 DHARMA CARAKA - Siti Kurniawati Giawa (Universitas Nias Raya, 2026)
Problem in this research is the violation of the principle of cooperation in student conversations in Indonesian language learning. This research was motivated by the researcher's curiosity about the use of the principle of cooperation. This research aims to describe violations of the principle of cooperation in conversation in Indonesian language learning for class VIII students at SMP Negeri 3 Dharma Caraka for the 2023/2024 academic year. The type of research used in this research is a qualitative approach with descriptive methods. The data collection technique used by researchers is documentation techniques. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. In this research, the data validity checking technique used was time triangulation. The results of this research are that in the conversation on the maxim of quantity there are 2 violations, in the conversation on the maxim of quality there are 2 violations, then in the conversation on the maxim of relevance there are 2 violations, on the maxim of implementation there are 2 violations, on the double maxim of quantity-relevance there is 1 violation, on the double maxim of implementation-quantity there are violations in student conversations in Indonesian language learning. among others; Violations in this conversation occur because students still do not understand the use of the principle of cooperation. Suggestions for researchers For other prospective researchers who will conduct further research regarding violations of the principle of cooperation in conversation in Indonesian language learning, it is recommended to conduct deeper, more thorough and more detailed research regarding violations of the principle of cooperation in conversation in Indonesian language learning regarding maxims Quantity, quality, relevance and implementation are recommended for future researchers who can use this research as reference material for conducting subsequent research.